Metodologi Penemuan Hukum Islam - Munawir Haris (Universitas Islam Negeri Mataram, 2012)
Continuous dialogue between Islamic law and its context of space and time necessitates the emergence of various methods of invention of Islamic law. This paper aims to map the diversity of the methods under some categorizations. The authors found that, at least, there are three models of methods of Islamic law invention, namely linguistic interpretation, causation, and adjustment. All are so strong in their trend of textual understanding of Islamic law that they potentially bring out epistemological problem, such as the law construction which is too idealistic so that it be not applicable, or vice versa. In that context, Safi offers a method of law invention called “integrated” model which is discovery-oriented blending of textual (normative-textual) and contextual analysis (social-empirical), so that Islamic law does not lose its relevance in the context contemporary society today.